The use of isoxazoline and isoxazole scaffolding in the design of novel thiourea and amide liquid-crystalline compounds - Gonçalves, Itamar L.; da Rosa, Rafaela R.; Eifler-Lima, Vera L.; Merlo, Aloir A. (Beilstein Journal of Organic Chemistry, 2020)
A series of novel thiourea and amide liquid crystals containing 5-membered isoxazoline and isoxazole rings were synthetized and the liquid crystal properties studied. Thioureas were obtained using a condensation reaction of benzoyl chlorides, arylamines and ammonium thiocyanate. The amides, on the other hand, were the byproduct of a quantitative reaction which used potassium cyanate as the starting material. Thiourea and amide derivatives were predominantly SmA mesophase inductors. A nematic mesophase was observed only for thioureas and amides containing an isoxazole ring. Additionaly, the liquid crystal behavior was also dependent on the relative position of nitrogen and oxygen atoms on the 5-membered heterocycle.
Keywords: amides; isoxazole; isoxazoline; liquid crystal; thiourea

(untitled) - Gonçalves, I. L.; de Azambuja, G. O.; Kawano, D. F.; Eifler-Lima, V. L. (Mini-Rev. Org. Chem., 2018)

(untitled) - Štrukil, V. (Beilstein J. Org. Chem., 2017)

(untitled) - Andrés, J. M.; Ceballos, M.; Maestro, A.; Sanz, I.; Pedrosa, R. (Beilstein J. Org. Chem., 2016)

(untitled) - Bielenica, A.; Stefańska, J.; Stępień, K.; Napiórkowska, A.; Augustynowicz-Kopeć, E.; Sanna, G.; Madeddu, S.; Boi, S.; Giliberti, G.; Wrzosek, M.; Struga, M. (Eur. J. Med. Chem., 2015)

(untitled) - Makam, P.; Kannan, T. (Eur. J. Med. Chem., 2014)

(untitled) - Zalavadiya, P. D.; Ghetiya, R. M.; Dodiya, B. L.; Vekariya, P. B.; Joshi, H. S. (J. Heterocycl. Chem., 2013)

(untitled) - Gonçalves, I. L.; Rockenbach, L.; das Neves, G. M.; Göethel, G.; Nascimento, F.; Porto Kagami, L.; Figueiró, F.; Oliveira de Azambuja, G.; de Fraga Dias, A.; Amaro, A.; de Souza, L. M.; da Rocha Pitta, I.; et al. (Med. Chem. Commun., 2018)

(untitled) - Gonçalves, I. L.; Davi, L.; Rockenbach, L.; das Neves, G. M.; Kagami, L. P.; Canto, R. F. S.; Figueiró, F.; Battastini, A. M. O.; Eifler-Lima, V. L. (Tetrahedron Lett., 2018)

(untitled) - Azizi, N.; Khajeh-Amiri, A.; Ghafuri, H.; Bolourtchian, M. (Mol. Diversity, 2011)

(untitled) - Kato, T.; Hirai, Y.; Nakaso, S.; Moriyama, M. (Chem. Soc. Rev., 2007)

(untitled) - Custelcean, R. (Chem. Commun., 2008)

(untitled) - Kishikawa, K.; Nakahara, S.; Nishikawa, Y.; Kohmoto, S.; Yamamoto, M. (J. Am. Chem. Soc., 2005)

(untitled) - Glettner, B.; Hein, S.; Reddy, R. A.; Baumeister, U.; Tschierske, C. (Chem. Commun., 2007)

(untitled) - Iliş, M.; Bucos, M.; Dumitraşcu, F.; Cîrcu, V. (J. Mol. Struct., 2011)

(untitled) - Sangeetha, N. M.; Maitra, U. (Chem. Soc. Rev., 2005)

(untitled) - Duarte, R. da C.; Ongaratto, R.; Piovesan, L. A.; de Lima, V. R.; Soldi, V.; Merlo, A. A.; D’Oca, M. G. M. (Tetrahedron Lett., 2012)

(untitled) - Andreis, M.; Carić, D.; Vujičić, N. Š.; Jokić, M.; Žinić, M.; Kveder, M. (Chem. Phys., 2012)

(untitled) - Yu, X.; Chen, H.; Shi, X.; Albouy, P.-A.; Guo, J.; Hu, J.; Li, M.-H. (Mater. Chem. Front., 2018)

(untitled) - Fritsch, L.; Merlo, A. A. (ChemistrySelect, 2016)

(untitled) - Tavares, A.; Toldo, J. M.; Vilela, G. D.; Gonçalves, P. F. B.; Bechtold, I. H.; Kitney, S. P.; Kelly, S. M.; Merlo, A. A. (New J. Chem., 2016)

Isoxazolinas e isoxazóis como reais candidatos na preparação de cristais líquidos polares - da Rosa, R. R. (Universidade Federal do Rio Grande do Sul, 2018)

(untitled) - Lopes, L. D.; Merlo, A. A. (Mol. Cryst. Liq. Cryst., 2015)

(untitled) - Vilela, G. D.; da Rosa, R. R.; Schneider, P. H.; Bechtold, I. H.; Eccher, J.; Merlo, A. A. (Tetrahedron Lett., 2011)

(untitled) - Tavares, A.; Ritter, O. M. S.; Vasconcelos, U. B.; Arruda, B. C.; Schrader, A.; Schneider, P. H.; Merlo, A. A. (Liq. Cryst., 2010)

(untitled) - Schneider, J. M. F. M.; Sales, E. S.; Livotto, P. R.; Schneider, P. H.; Merlo, A. A. (J. Braz. Chem. Soc., 2014)

Liquid Crystals - Tschierske, C. (Fluorinated Liquid Crystals: Design of Soft Nanostructures and Increased Complexity of Self-Assembly by Perfluorinated Segments, 2011)

(untitled) - Fritsch, L.; Baptista, L. A.; Bechtold, I. H.; Araújo, G.; Mandle, R. J.; Merlo, A. A. (J. Mol. Liq., 2020)

(untitled) - Bushby, R. J.; Lozman, O. R. (Curr. Opin. Colloid Interface Sci., 2002)

(untitled) - Hariprasad, S.; Srinivasa, H. T. (Liq. Cryst., 2015)

(untitled) - Lu, L.-Y.; Kuo, H.-M.; Sheu, H.-S.; Lee, G.-H.; Lai, C. K. (Tetrahedron, 2014)

(untitled) - Pongali Sathya Prabu, N.; Madhu Mohan, M. L. N. (Phase Transitions, 2013)

(untitled) - Rajanandkumar, R.; Prabu, N. P. S.; Mohan, M. L. N. M. (Mol. Cryst. Liq. Cryst., 2016)